Regulation of ΔFosB Stability by Phosphorylation - Ulery, Paula G. (J Neurosci, 2006)
The transcription factor ΔFosB (also referred to as FosB2 or FosB[short form]) is an important mediator of the long-term plasticity induced in brain by chronic exposure to several types of psychoactive stimuli, including drugs of abuse, stress, and electroconvulsive seizures. A distinct feature of ΔFosB is that, once induced, it persists in brain for relatively long periods of time in the absence of further stimulation. The mechanisms underlying this apparent stability, however, have remained unknown. Here, we demonstrate that ΔFosB is a relatively stable transcription factor, with a half-life of ∼10 h in cell culture. Furthermore, we show that ΔFosB is a phosphoprotein in brain and that phosphorylation of a highly conserved serine residue (Ser27) in ΔFosB protects it from proteasomal degradation. We provide several lines of evidence suggesting that this phosphorylation is mediated by casein kinase 2. These findings constitute the first evidence that ΔFosB is phosphorylated and demonstrate that phosphorylation contributes to its stability, which is at the core of its ability to mediate long-lasting adaptations in brain.